ANALISIS BIAYA PENGADAAN AKTIVA TETAP DENGAN MENGGUNAKAN ALTERNATIF LEASING DAN HUTANG JANGKA PANJANG PADA PT. KERETA API INDONESIA (PERSERO) - Sandy Etika Susanto; Evaliati Amaniyah; - Purnamawati (Eco-Entrepreneur, 2015)
Purpose of this study is to determine which one is more efficient to finance fixed asset by using leasing and long term debt at PT. Kereta Api Indonesia (Persero). The method used in this study is descriptive method. This study use net present value to compare efficiency between leasing and long term debt. The result of this study is long term debt more profitable than leasing. This is because long term debt has smaller net present value is 366.441.097.703 than net present value of leasing is 452.327248.432